Changes in prostate cancer incidence, mortality and survival in relation to prostate specific antigen testing in New South Wales, Australia. (June 2022) - Luo, Qingwei; Yu, Xue Qin; Kahn, Clare; Egger, Sam; Patel, Manish I.; Grogan, Paul B.; Caruana, Michael; Canfell, Karen; Smith, David P.; O'Connell, Dianne L.
Abstract: Background: To examine changes in prostate cancer incidence and mortality rates, and 5-year relative survival, in relation to changes in the rate of prostate specific antigen (PSA) screening tests and the use of radical prostatectomy (RP) in the Australian population. Methods: Prostate cancer stage-specific incidence rates, 5-year relative survival and mortality rates were estimated using New South Wales Cancer Registry data. PSA screening test rates and RP/Incidence ratios were estimated from Medicare Benefits Schedule claims data. We used multiple imputation to impute stage for cases with "unknown" stage at diagnosis. Annual percentage changes (APC) in rates were estimated using Joinpoint regression. Results: Trends in the age-standardized incidence rates for localized disease largely mirrored the trends in PSA screening test rates, with a substantial 'spike' in the rates occurring in 1994, followed by a second 'spike' in 2008, and then a significant decrease from 2008 to 2015 (APC −6.7, 95% CI −8.2, −5.1). Increasing trends in incidence rates were observed for regional stage from the early 2000s, while decreasing or stable trends were observed for distant stage since 1993. The overall RP/Incidence ratio increased from 1998 to 2003 (APC 9.6, 95% CI 3.8, 15.6), then remained relatively stable to 2015. The overall 5-year relative survival for prostate cancer increased from 58.4% (95% CI: 55.0–61.7%) in 1981–1985 to 91.3% (95% CI: 90.5–92.1%) in 2011–2015. Prostate cancer mortality rates decreased from 1990 onwards (1990–2006: APC −1.7, 95% CI −2.1, −1.2; 2006–2017: APC −3.8, 95% CI −4.4, −3.1). Conclusions: Overall, there was a decrease in the incidence rate of localized prostate cancer after 2008, an increase in survival over time and a decrease in the mortality rate since the 1990s. This seems to indicate that the more conservative use of PSA screening tests in clinical practice since 2008 has not had a negative impact on population-wide prostate cancer outcomes. Highlights: Changes in PSA testing guidelines impacted Australian prostate cancer trends. PSA testing rates and rates of localized prostate cancer decreased from 2008. Distant stage prostate cancer rates fell or remained stable from 1993. From the 1990s, prostate cancer survival increased and the mortality rate decreased. No evidence of negative population-wide outcomes from reduced use of PSA testing.